1994
DOI: 10.1073/pnas.91.10.4254
|View full text |Cite
|
Sign up to set email alerts
|

Effector region of the translation elongation factor EF-Tu.GTP complex stabilizes an orthoester acid intermediate structure of aminoacyl-tRNA in a ternary complex.

Abstract: ABSTRACTtRNAvI from Escherichia coli was aminoacylated with [1-'3C]valine and its complex with Thermus thermophius elongation factor EF-Tu GTP was analyzed by 13C NMR spectroscopy. The results suggest that the aminoacyl residue of the valyl-tRNA in ternary complex with bacterial EF-Tu and GTP is not attached to tRNA by a regular ester bond to either a 2'-or 3'-hydroxyl group; instead, an intermediate orthoester acid structure with covalent linkage to both vicinal hydroxyls of the terminal adenosine-76 is forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…The electron density does not support a 2',3'-orthoester structure, as proposed on the basis of "C-NMR (nuclear magnetic resonance) experilnelnts on the ternary c o~n p l e~ (30). Furthermore, the ester bond is 26 A alvay from Arg5" ,which fails to support the suggestion that Arg5%ttahilizes the orthoester anion (30).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The electron density does not support a 2',3'-orthoester structure, as proposed on the basis of "C-NMR (nuclear magnetic resonance) experilnelnts on the ternary c o~n p l e~ (30). Furthermore, the ester bond is 26 A alvay from Arg5" ,which fails to support the suggestion that Arg5%ttahilizes the orthoester anion (30).…”
mentioning
confidence: 67%
“…Furthermore, the ester bond is 26 A alvay from Arg5" ,which fails to support the suggestion that Arg5%ttahilizes the orthoester anion (30). Other "C-NMR experiments have not detected the existence of an orthoester (31).…”
mentioning
confidence: 76%
“…Nevertheless, NMR studies of EF-Tu complex with tRNA reported that the protein can stabilize an orthoester intermediate between the two isomeric forms (27). QM/MM simulations of deacylation pathway for the TtPheRS complex with puromycin also testify that the labile hydroxyl will be locked into position by interactions with side chains and water molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, migration of the phenylalanine happens four orders of magnitude faster, thus suggesting that the equilibration rate depends on the chemical structure of the acyl group (31). The 2′→3′ transition proceeds via an intramolecular reaction with a formation of cyclic orthoester acid 2′,3′-intermediate of the aminoacyl residue (27). Fast transitions in 2′ ↔ 3′ isomers are associated with proton migration between hydroxyl groups accelerating in the presence of water molecules (30).…”
Section: Quantum Mechanics/molecular Mechanics Simulation and Its Strmentioning
confidence: 99%
See 1 more Smart Citation